Implementation of Boundary Alert system for Fishermen - et. al., S. Niveda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fishing is one of the main occupations of the people who live near the coastal areas. In order to satisfy their daily requirements, fishermen need to get more fish. Once fishermen are not satisfied at a certain place, they move to further places to acquire more fish. Sometimes, without their knowledge they cross the border. Due to this, the navy of the other country arrests him and sentence them to prison. This happens because there is no awareness of boundary for the fishermen. In order to create an awareness for the fishermen, we proposed a system. Our proposed systemwill be an alternate source for avoiding such kind of accidents andalert the fishermen about the border area. In addition to that, in our project we implemented automatic turning of the boat in desired direction even when the alarm system fails to alert the fishermen by using RFtechnology. This is done byfixing the receiver in the boat and the transmitter has to be placed before 100 meters from the IMBL (International Marine time Boundary Line). This can be used to avoid crossing the boundary.